A new dynamic guard channel reservation scheme for cellular wireless networks. (1st October 2010) - Samanta, Raj Kumar; Sanyal, Gautam; Bhattacharjee, Partha
In this paper, a new dynamic guard channel reservation scheme, based on conditional real-time channel availability, is proposed to achieve better handoff performance and higher utilisation of system resources (radio spectrum) in cellular wireless networks. The proposed scheme has been explained mathematically and studied in a cellular wireless environment. Different performance parameters are measured using the proposed scheme and are compared with those obtained from a fixed guard channel scheme.